The role of institutional pressures and organizational culture in the firm's intention to adopt internet‐enabled supply chain management systems - Liu, Hefu; Ke, Weiling; Wei, Kwok Kee; Gu, Jibao; Chen, Huaping (Journal of Operations Management, 2010)
AbstractDrawing upon organizational culture and institutional theory, this study investigates how institutional pressures motivate the firm to adopt Internet‐enabled Supply Chain Management systems (eSCM) and how such effects are moderated by organizational culture. The results of a survey of 131 firms suggest that the dimensions of institutional pressures (i.e., normative, mimetic, and coercive pressures) have differential effects on eSCM adoption intention. While mimetic pressures are not related to eSCM adoption intention, normative and coercive pressures are positively associated with eSCM adoption intention. In addition, organizational culture (i.e., flexibility orientation and control orientation) plays different roles in the relationships between these three dimensions of institutional pressures and eSCM adoption intention. While flexibility orientation negatively moderates the effects of coercive pressures and positively moderates the effects of mimetic pressures, control orientation positively moderates the effects of coercive and normative pressures and negatively moderates the effects of mimetic pressures. Implications and suggestions for future research are provided.